PEMBUATAN DAN PENGUJIAN PADA MESIN PENGIRIS BAWANG - Edison Edison; Afridon As (Menara Ilmu, 2020)
In the progress of this modern era, every human being is required to be able to think innovatively and creatively in order to create a tool to support human needs themselves. As an action taken by humans in facilitating a job that they do and to get results in accordance with what they plan. So engine planning is really needed in it. Human needs are increasingly increasing require us to work even harder to meet those needs, while the amount of energy produced by humans is very limited, so that requires us as potential successors to be able to create or design a tool to support a job so that the work become easy and obtain maximum results so that it meets the needs of human life. The aim of the research is to create a home-scale industrial onion slicing machine that is easy to operate. On a finished onion slicing machine six tests and data retrieval and data processing can be done into reports. The results of research carried out by varying the density of the knife, the first experiment where the onion was 1 kg where the speed ( ) 608 Rpm and the blade density of 1 mm with a slicing time of 3.30 minutes, in the second experiment with a density of 2 mm, the slicing time obtained is 1.17 minutes, on the third try with a density of 3 mm, the time obtained is 0.30 minutes. In the test by varying the rotation ( ), in the first experiment that is round ( ) 608.6 with the same density of 2 mm, the time obtained was 1.17 rpm minutes, in the second experiment with the rotation ( ) 304.7 rpm with time the cutting was 1.52 minutes, in the third experiment with rotation ( ) 207.5 rpm and the time obtained was 2.21 minutes and in the fourth experiment with rotation ( ) 114.3 rpm with the cutting time 3.39 minutes. Keywords: onion slicer and onion slicing machine.